2012
DOI: 10.1590/s1679-45082012000200022
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial sonography in Parkinson's disease

Abstract: Transcranial sonography has become a useful tool in the differential diagnosis of parkinsonian syndromes. This is a non-invasive, low cost procedure. The main finding on transcranial sonography in patients with idiopathic Parkinson's disease is an increased echogenicity of the mesencephalic substantia nigra region. This hyperechogenicity is present in more than 90% of cases, and reflects a dysfunction in the dopaminergic nigrostriatal pathway. This study discussed how the hyperechogenicity of the substantia ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
2
0
1
Order By: Relevance
“…11,12 Transcranial Sonography in PD and Atypical Parkinsonian Syndromes Substantia nigra hyperechogenicity above the cutoff value as a typical finding in patients with PD ( Figure 1) was first described by Becker et al 1 Substantia nigra hyper echogenicity could be found unilaterally or asymmetrically bilaterally. This finding has been also shown by many other research groups over the last decades (for reviews, see Gaenslen and Berg 16 and Bor-Seng-Shu et al 17 ).…”
Section: A C Bsupporting
confidence: 79%
“…11,12 Transcranial Sonography in PD and Atypical Parkinsonian Syndromes Substantia nigra hyperechogenicity above the cutoff value as a typical finding in patients with PD ( Figure 1) was first described by Becker et al 1 Substantia nigra hyper echogenicity could be found unilaterally or asymmetrically bilaterally. This finding has been also shown by many other research groups over the last decades (for reviews, see Gaenslen and Berg 16 and Bor-Seng-Shu et al 17 ).…”
Section: A C Bsupporting
confidence: 79%
“…Cerebral vasomotor reactivity (CVR) was evaluated by measuring the breath holding index (BHI) [ 33 ]. The hyperechogenic area at the SN was measured automatically by encircling the outer circumference of the area of ​​hyperechogenicity, and the highest value was recorded [ 34 ]. Patients with at least one echogenic size ≥ 18 mm 2 were classified as hyperechogenic [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Compared to controls, results showed that patients with tremulant form of PD had greater ALFF in the posterior cerebellum contralateral to the more affected side by tremor. 15 Enod= Nodal efficiency 16 Ndeg= Nodal degree 17 NBet= Nodal betweeness 18 Cp= Clustering coefficient 19 Lp= Path Lenght 20 Eloc= Local Efficiency Since PD is associated with a reduction of the motor activity, and based on the previous studies which, in its majority, pointed out to a decreased global efficiency, our hypothesis was more driven towards a diminished GE of the motor network in PD in comparison to controls.…”
Section: Pairwise Metrics Studies In Pdmentioning
confidence: 84%